A practical guideline for performing a comprehensive transthoracic echocardiogram in adults: the British Society of Echocardiography minimum dataset. Issue 4 (December 2020) - Robinson, Shaun; Rana, Bushra; Oxborough, David; Steeds, Rick; Monaghan, Mark; Stout, Martin; Pearce, Keith; Harkness, Allan; Ring, Liam; Paton, Maria; Akhtar, Waheed; Bedair, Radwa; et al.
Abstract : Since cardiac ultrasound was introduced into medical practice around the middle twentieth century, transthoracic echocardiography has developed to become a highly sophisticated and widely performed cardiac imaging modality in the diagnosis of heart disease. This evolution from an emerging technique with limited application, into a complex modality capable of detailed cardiac assessment has been driven by technological innovations that have both refined 'standard' 2D and Doppler imaging and led to the development of new diagnostic techniques. Accordingly, the adult transthoracic echocardiogram has evolved to become a comprehensive assessment of complex cardiac anatomy, function and haemodynamics. This guideline protocol from the British Society of Echocardiography aims to outline the minimum dataset required to confirm normal cardiac structure and function when performing a comprehensive standard adult echocardiogram and is structured according to the recommended sequence of acquisition. It is recommended that this structured approach to image acquisition and measurement protocol forms the basis of every standard adult transthoracic echocardiogram. However, when pathology is detected and further analysis becomes necessary, views and measurements in addition to the minimum dataset are required and should be taken with reference to the appropriate British Society of Echocardiography imaging protocol. It is anticipated that the recommendations made within this guideline will help standardise the local, regional and national practice of echocardiography, in addition to minimising the inter and intra-observer variation associated with echocardiographic measurement and interpretation.